A Lamaze guide for the Philippines - Dorros, Sybilla Green 1946- (Quezon City Adriana Printing, 1981)
Gives factual and comprehensive information about Lamaze preparation for childbirth. It provides a step-by-step guide from the 9 month process of handling the child properly inside the womb up to the actual labor of the mother. This guide tackles and emphasizes the Filipino style of Lamaze childbirth.
Keywords: Natural childbirth -- Philippines